Fetal intracranial hemorrhage: sonographic criteria and merits of prenatal diagnosis. (17th September 2017) - Abdelkader, Mohamed Ali; Ramadan, Wafaa; Gabr, Amir A.; Kamel, Ahmed; Abdelrahman, Rasha W.
Abstract: Purpose : To determine the sonographic criteria for diagnosis of fetal intracranial hemorrhage (ICH), using both gray scale ultrasound, and tomographic ultrasound imaging (TUI). Materials and methods : A prospective multicenter study, recruiting patients at risk of fetal ICH over four years. All cases with fetal ICH had serial ultrasound assessments, including TUI, fetal and postnatal MRIs. Results : Twenty-one patients were diagnosed with fetal ICH, two cases had extracerebral (subdural) hemorrhage, 16 cases had intracerebral (intraventricular) hemorrhage and three cases had combined hemorrhage. The mean gestational age at which they were diagnosed was 29.8 ± 5.2 weeks. Seventy-six percent of cases had no identifiable risk factors. IUGR was associated with 57.9% of cases. Using grey scale ultrasound, we demonstrated clear cut sonographic criteria for diagnosis of fetal ICH. TUI enabled us to detect some midline cerebral lesions not detected by grey scale 2D ultrasound alone. Fetal and postnatal MRI confirmed those findings. Conclusion : Ultrasonography can be used in the detection, classification and monitoring the progression of various types of ICH. TUI is an additional diagnostic tool that might help to detect the exact size, and extent of those lesions. Fetal MRI is not superior, but might aid in the diagnosis.